2021
DOI: 10.1038/s41523-021-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

The tale of TILs in breast cancer: A report from The International Immuno-Oncology Biomarker Working Group

Abstract: The advent of immune-checkpoint inhibitors (ICI) in modern oncology has significantly improved survival in several cancer settings. A subgroup of women with breast cancer (BC) has immunogenic infiltration of lymphocytes with expression of programmed death-ligand 1 (PD-L1). These patients may potentially benefit from ICI targeting the programmed death 1 (PD-1)/PD-L1 signaling axis. The use of tumor-infiltrating lymphocytes (TILs) as predictive and prognostic biomarkers has been under intense examination. Emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 120 publications
(187 reference statements)
8
95
0
1
Order By: Relevance
“…The prognostic significance of TILs in TNBC and HER2+ breast cancer has been extensively studied, and the presence of TILs in the intratumoral stroma is associated with a more favorable prognosis [ 7 , 8 ]. In ER+/HER2− breast cancer, a subtype normally less immunogenic than TNBC and HER+ breast cancer, the prognostic role of TILs is not fully elucidated, although several studies suggest that the presence of TILs is associated with a less favorable prognosis [ 7 ]. Furthermore, in ILC, only a small fraction of the tumors have TILs, and the levels are generally lower than in NST [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic significance of TILs in TNBC and HER2+ breast cancer has been extensively studied, and the presence of TILs in the intratumoral stroma is associated with a more favorable prognosis [ 7 , 8 ]. In ER+/HER2− breast cancer, a subtype normally less immunogenic than TNBC and HER+ breast cancer, the prognostic role of TILs is not fully elucidated, although several studies suggest that the presence of TILs is associated with a less favorable prognosis [ 7 ]. Furthermore, in ILC, only a small fraction of the tumors have TILs, and the levels are generally lower than in NST [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that stromal cells (e.g., pericytes and fibroblasts) integrate with cancer cells and can affect tumor progression via paracrine signaling, which stimulates tumor growth and angiogenesis [ 6 ]. Tumor infiltrating lymphocytes (TILs) in the intratumoral stroma interact with cancer cells via complex immune-mediated mechanisms, and the presence of TILs is associated with prognostic outcome in breast cancer [ 7 , 8 ]. To date, there is no strict consensus on how to assess the relationship between stromal content and cancer cells in tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The number and type of tumor-infiltrating lymphocytes (TILs) and other immune cells present in the tumor microenvironment are also relevant for an immune antitumor response. Tumors are categorized as hot when a high number of TILs are present inside the tumor stroma, immune excluded when immune cells are present in the periphery of the tumor but not penetrating between the tumor cells, and cold when immune cells are completely absent [ 41 ]. A high number of TILs has been associated with a better prognosis and response to immune therapies [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second states that “in patients with advanced/recurrent TNBC, TILs should be quantified …” (Section VIII). This was added as PD-L1 testing in breast cancer is not easily available and is not funded in NZ, therefore quantification of TILs could be a good way to select candidates for unfunded immunotherapy with PD-(L)1 inhibitors [ [9] , [10] , [11] , [12] ]. We also added that “in patients with advanced/recurrent TNBC, PD-L1 status (assays SP142 Ventana assay >1% or more) should be assessed as well” [ 9 ] (Section VIII) to assess the willingness of physicians to use or request this test.…”
Section: Discussionmentioning
confidence: 99%
“…This was added as PD-L1 testing in breast cancer is not easily available and is not funded in NZ, therefore quantification of TILs could be a good way to select candidates for unfunded immunotherapy with PD-(L)1 inhibitors [ [9] , [10] , [11] , [12] ]. We also added that “in patients with advanced/recurrent TNBC, PD-L1 status (assays SP142 Ventana assay >1% or more) should be assessed as well” [ 9 ] (Section VIII) to assess the willingness of physicians to use or request this test. Finally, we added a guideline recommending a single 8 Gy fraction for uncomplicated symptomatic bone metastasis (Section IX) to have our guidelines line up with recommendations made by radiation oncologists in NZ (as explained in Table 1 ) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%